2006
DOI: 10.1007/s00429-006-0136-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of cerebral sulci and gyri in fetuses of cynomolgus monkeys (Macaca fascicularis)

Abstract: This study aimed to clarify the development of sulci and gyri on the external surface of the cerebrum of cynomolgus monkeys. Sulcus formation began with the appearance of the lateral fissure on embryonic day (ED) 70, followed by delineations of four cerebral lobes by the emergence of the parietooccipital sulcus, central sulcus, and preoccipital notch on EDs 80-90. The following primary sulci were then visible until ED 120: the superior temporal sulcus on ED 90; the intraparietal sulcus, lunate sulcus, inferior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
65
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(74 citation statements)
references
References 21 publications
9
65
0
Order By: Relevance
“…7.4 in our previous study (Fukunishi et al 2006). Photographs of the medial surface of the cerebrum were taken, and tracings were made from the photographs of the outlines of the perimeter of the hemisphere and of the sulcal patterns at each age.…”
Section: Observations Of Development Of Cerebral Sulci and Gyrisupporting
confidence: 51%
See 4 more Smart Citations
“…7.4 in our previous study (Fukunishi et al 2006). Photographs of the medial surface of the cerebrum were taken, and tracings were made from the photographs of the outlines of the perimeter of the hemisphere and of the sulcal patterns at each age.…”
Section: Observations Of Development Of Cerebral Sulci and Gyrisupporting
confidence: 51%
“…Photographs of the medial surface of the cerebrum were taken, and tracings were made from the photographs of the outlines of the perimeter of the hemisphere and of the sulcal patterns at each age. According to the procedures of our study (Fukunishi et al 2006), the degree of sulcal formation was graded three as shown in Fig. 1, with its chronological order appearing in Table 1.…”
Section: Observations Of Development Of Cerebral Sulci and Gyrimentioning
confidence: 99%
See 3 more Smart Citations